Shifting Learning in to Mobile Learning and Teachers’ Attitude towards it. - Gupta, Nitin Kumar; Vishwakarma, Dr.V.P. (IJRDO- Journal of Educational Research, 2017)
The potential of Mobile phone technology huge and it has broken ground for enhancingknowledge, in higher education. however, it was found that there was lack of academicresearches on the use of mobile phone technology for knowledge sharing process ineducational system. Today’s teacher must be updated with innovative technology likemobile technology if they want to sustain in the field of education. There is a lack ofawareness of mobile learning among most of the teachers in our country. We have writtenthis paper after reviewing some papers related to Mobile learning and it has been foundthat using Mobile devices in the classrooms scenario and other educational purposes playan important role in enhancing learning. It has also been found that teachers and studentshave positive attitude towards mLearning in foreign countries and our country also. Soresearchers’ main objective was to give emphasis on using the mobile devices in oureducation system.